Intercountry prevalences and practices of betel-quid use in south, southeast and eastern asia regions and associated oral preneoplastic disorders: an international collaborative study by asian betel-quid consortium of south and east Asia - Lee, C.H.; Ko, A.M.S.; Warnakulasuriya, S.; Yin, B.L.; Sunarjo, .; Zain, R.B.; Ibrahim, S.O.; Liu, Z.W.; Li, W.H.; Zhang, S.S.; Kuntoro, .; Utomo, B.; et al. (John Wiley & Sons, 2011)
Health risks stemming from betel-quid (BQ) chewing are frequently overlooked by people. Updated epidemiological data on the increased BQ use among Asian populations using comparable data collection methods have not been widely available. To investigate the prevalence, patterns of practice and associated types of oral preneoplastic disorders, an intercountry Asian Betel-quid Consortium study (the ABC study) was conducted for Taiwan, Mainland China, Malaysia, Indonesia, Nepal and Sri Lanka. A random sample of 8,922 subjects was recruited, and the data were analyzed using survey-data modules adjusted for the complex survey design. Chewing rates among men (10.7-43.6) were significantly higher than women (1.8-34.9) in Taiwan, Mainland China, Nepal and Sri Lanka, while women's rates (29.5-46.8) were higher than that for men (9.8-12.0) in Malaysia and Indonesia. An emerging, higher proportion of new-users were identified for Hunan in Mainland China (11.1-24.7), where Hunan chewers have the unique practice of using the dried husk of areca fruit rather than the solid nut universally used by others. Men in the Eastern and South Asian study communities were deemed likely to combine chewing with smoking and drinking (5.6-13.6). Indonesian women who chewed BQ exhibited the highest prevalence of oral lichen planus, oral submucous fibrosis and oral leukoplakia (9.1-17.3). Lower schooling, alcohol drinking and tobacco smoking were identified as being associated with BQ chewing. In conclusion, the ABC study reveals the significant cultural and demographic differences contributing to practice patterns of BQ usage and the great health risks that such practices pose in the Asian region.